Analysis Of The Effect Of Job Satisfaction On Employee Performance In The Aceh Health Service - Erlinawati; Fajar Rezeki Ananda Lubis; Syaifuddin (Cita konsultindo, 2026)
The Aceh Health Office is one of the Aceh Government's Work Units (SKPA) tasked with carrying out general government duties in the areas of disease control and environmental health, health service development, health resource development, and pharmaceuticals, in accordance with laws and regulations. Through preliminary tests and interviews, issues related to job satisfaction were identified within the Aceh Health Office. This study aims to examine the level of job satisfaction and staff performance, as well as the impact of job satisfaction on staff performance, using a case study of the finance and asset management team. Based on the analysis of the influence of job satisfaction on staff performance in the finance and asset management team, the researchers obtained descriptive results indicating that job satisfaction is categorized as high, and employee performance is also categorized as high. The relationship between the variables has a positive and significant effect, accounting for 17.4% of the impact, while the remaining 82.6% is influenced by other factors not analyzed in this study. In conclusion, the researchers found a positive and significant relationship between job satisfaction and staff performance in the finance and asset management team at the Aceh Health Office.